Spatial distribution of selected genetic loci in nuclei of human leukemia cells after irradiation - Kozubek, S; Bártová, E; Kozubek, M; Lukásová, E; Cafourková, A; Koutná, I; Skalníková, M (Radiation research, 2001)
Fluorescence in situ hybridization (FISH) combined with high-resolution cytometry was used to determine the topographic characteristics of the centromeric heterochromatin (of the chromosomes 6, 8, 9, 17) and the tumor suppressor gene TP53 (which is located on chromosome 17) in cells of the human leukemia cell lines ML-1 and U937. Analysis was performed on cells that were either untreated or irradiated with gamma rays and incubated for different intervals after exposure. Compared to untreated cells, homologous centromeres and the TP53 genes were found closer to each other and also closer to the nuclear center 2 h after irradiation. The spatial relationship between genetic elements returned to that of the unirradiated controls during the next 2-3 h. Statistical evaluation of our experimental results shows that homologous centromeres and the homologous genes are positioned closer to each other 2 h after irradiation because they are localized closer to the center of the nucleus (probably due to more pronounced decondensation of the chromatin related to repair). This radial movement of genetic loci, however, is not connected with repair of DSBs by processes involving homologous recombination, because the angular distribution of homologous sequences remains random after irradiation.
Keywords: lidské chromozomy; poškození DNA; leukemie; Neoplastic Stem Cells; Cell Nucleus; centromera; DNA Damage; hybridizace in situ fluorescenční; Centromere; heterochromatin; Image Processing, Computer-Assisted; buněčné jádro; geny; Gamma Rays; Genes; DNA Repair; oprava DNA; počítačové zpracování obrazu; Leukemia; lidé; Heterochromatin; Humans; Recombination, Genetic; U937 Cells; rekombinace genetická; In Situ Hybridization, Fluorescence; Chromosomes, Human; nádorové kmenové buňky; záření gama; U937 buňky